2012
DOI: 10.1186/1471-2458-12-800
|View full text |Cite
|
Sign up to set email alerts
|

Association of violence against women with religion and culture in Erbil Iraq: a cross-sectional study

Abstract: BackgroundViolence against women by intimate partners is still a public health problem. The study aims at finding out the prevalence of violence among women residing in Erbil city (Muslim culture) and in Ankawa sub-district (Christian culture), finding out the role of religion and culture on the prevalence, and finding out some other factors (like occupation of husband and wife, age at marriage, woman agreement for marriage, illegitimate relations of husband) that might be associated with violence.MethodsA cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 17 publications
1
24
0
Order By: Relevance
“…Among the 21 surveys reported in journals that used or adapted international instruments, at least ten used WHO instruments [23, 27, 60, 61, 71, 75, 84–86], three used DHS questionnaires [20, 28, 30], and four [6668, 78] used the Abuse Assessment Screen (AAS) or the Women’s Abuse Screening Tool (WAST) (Additional file 1). DHS reports included definitions and full questionnaires.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 21 surveys reported in journals that used or adapted international instruments, at least ten used WHO instruments [23, 27, 60, 61, 71, 75, 84–86], three used DHS questionnaires [20, 28, 30], and four [6668, 78] used the Abuse Assessment Screen (AAS) or the Women’s Abuse Screening Tool (WAST) (Additional file 1). DHS reports included definitions and full questionnaires.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the item on spousal violence is ranked ‘-4’ in Factor 1 and Factor 2 suggesting most if not all women here did not experience it, whereas it is ranked ‘1’ in Factor 3 and Factor 4 suggesting the responses were averaged with some did and some did not experience it. While intimate partner violence against women is common in Iraqi Kurdistan region [ 53 , 54 ], the question of spousal violence could not help to determine its effect on women’s experience with pregnancy and antenatal care. Factual items like this would have been better asked as part of a survey and used to contextualize the factor interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the proportion of male-to-female partner violence is higher than that of female-to-male partner violence. Previous studies have found that culture is an important predictor of violence against women [13,14]. Compared to western societies, in Asian countries, women often follow cultural norms and values in male-dominated society and tend not to disclose abuse to the public [15].…”
Section: Introductionmentioning
confidence: 99%